Perceptions and attitudes of healthcare workers towards the use of digital facial recognition application in a health setting in Uganda: An exploratory pilot study - Patrick Kaggwa; Juliet Nabbuye Sekandi; Mcdonald Kerone Adenike; Peter Nabende; Sarah Nabukeera; Kenneth Kidonge Katende; Esther Buregyeya; Nazarius Mbona Tumwesigye (PLoS ONE, 2025)
Background Unique patient identification is often challenging in healthcare systems, especially in low- and middle-income countries. Digital facial recognition is a promising alternative to traditional identification methods. This pilot study explores the perceptions and attitudes of healthcare workers towards using facial recognition technology in a healthcare setting in Uganda. Methods We conducted an explorative qualitative study using key informant interviews with healthcare workers in Kampala, Uganda, to assess perceptions and attitudes towards digital facial recognition. We interviewed a total of 10 healthcare workers, including five doctors and five nurses, aged 20–39 years, with at least one year of professional experience. A trained interviewer provided a brief overview and demonstration of the facial recognition application and then used an open-ended interview guide to elicit responses about perceptions and attitudes. The interviews were audio recorded and transcribed verbatim. Data obtained from Key Informant Interviews were manually analyzed using thematic content analysis. Results Overall, the healthcare workers perceived digital facial recognition as a more effective and acceptable way to identify patients who receive service at outpatient clinics. Four themes emerged, including: i) Challenges affecting current patient identification standards, ii) Healthcare workers’ views on facial recognition, iii) Perceived digital facial recognition implementation challenges, and iv) Solutions to challenges of digital facial recognition. The healthcare workers recommended ensuring the protection patients’ images privacy, providing adequate technological infrastructure in clinics, and securing stable internet access for the successful implementation of digital facial recognition. Conclusion Our exploratory study indicates that overall, healthcare workers have a positive perception of the digital facial recognition application. However, it is crucial to acknowledge and address concerns regarding confidentiality and privacy to pave the way for the future implementation of the system.